Self-Efficacy Guru Sebagai Determinan Implementasi Project-Based Learning Di Sekolah Menengah - Wiwit Laraswati Lase; Erni Murniarti (LPPM Institut Pendidikan Nusantara Global, 2026)
The implementation of Project-Based Learning (PjBL) in secondary schools requires teacher readiness in pedagogical practice and confidence in managing student-centered learning. This study aims to examine the effect of teacher self-efficacy on the implementation of Project-Based Learning at PSKD. The research used a quantitative survey approach involving 102 active teachers selected through saturated sampling. Data were collected using a closed-ended questionnaire with a four-point Likert scale and analyzed through simple linear regression. The results show that teacher self-efficacy has a positive and significant effect on PjBL implementation, as indicated by an R Square value of 0.511 and a significance value of 0.001. These findings indicate that teachers with stronger professional confidence are more capable of planning, guiding, and evaluating project-based learning. The study implies that strengthening teacher self-efficacy through practice-based training, academic supervision, mentoring, and collaborative reflection is important for improving innovative learning in secondary schools.